NEW CHALLENGES FOR TRADE PROMOTION ACTIVITY IN ACTUAL GLOBAL WORLD ECONOMIC FRAMEWORK - Octavian-Liviu OLARU (Challenges of the Knowledge Society, 2015)
Export promotion strategy has to play play an important part in the development strategies of countries, especially of developing countries that seek to make exports an engine for economic growth. General category of Trade support institutions (TSI) exist in every country to help businesses developement, promote and sell their goods and services abroad. Within TSI, we can consider that a TPO traditionally has a the leading role in “promoting” international trade, focusing on the most important activities in the field, in cooperation with the other component institutions of a national TSI. There may be more than one TPO per country, they are not homogeneous and can take many forms. There has not been a revolution in trade promotion activity over the the past 20 years, but there has certainly been an evolution in the context of new prerequisits of the global world economic framework).